RESOLUSI KONFLIK MASYARAKAT PINGGIRAN (Studi Kasus: Kepemilikan Tanah Leluhur Di Desa Leppangeng Kecamatan Pitu Riase Kabupaten Sidenreng Rappang) - Barisan, Barisan; B, Sofian (UIR PRESS, 2019)
This study aims to analyze conflicts over ancestral land ownership in Leppangeng Village, Pitu Riase District, Sidenreng Rappang Regency. The research approach used is descriptive qualitative. This study concludes that conflicts over ancestral land ownership in Leppangeng Village have an impact on the estrangement of relations between relatives in the community. Difficulties in finding solutions to these problems are the lack of an active role from the village government and the absence of interference from local traditional leaders in this case sando batu and all of his staff.